Phytochemical analysis, antioxidant and antibacterial activities of methanolic rhizome extract of Bergenia pacumbis: A valuable medicinal herb - Dangi, Subas; Parajuli, Niranjan (BIBECHANA, 2022)
Bergenia pacumbis, a perennial herb of the Saxifragaceae family, usually referred to as ‘Pashanbheda’ is geographically distributed within the temperate Himalaya including Nepal. The purpose of this study was to evaluate the phytochemical analysis as well as in vitro antioxidant and antibacterial activities of methanolic rhizome extract of B. pacumbis. The rhizome of B. pacumbis was extracted in methanol using the Soxhlet apparatus and then the extract was concentrated. The rhizome extract was tested for phytochemicals using the standard protocol. The in vitro antioxidant activity of the extract was evaluated using the 2, 2- diphenyl-1-picrylhydrazyl free radical scavenging assay. The 50 % inhibitory concentration (IC50) values of ascorbic acid and B. pacumbis were found to be 11.91 ± 0.03 μg/mL and 11.99 ± 0.05 μg/mL respectively that indicate B. pacumbis is a good source of antioxidant agents. The extract was further tested for antibacterial activity through the agar well diffusion method and found to be effective against Staphylococcus aureus (16 mm) and Klebsiella pneumoniae (12 mm). The present study validates the traditional use of B. pacumbis. BIBECHANA 19 (2022) 14-26